Calcaneal Displacement Osteotomies - Less Soft Tissue Irritation in Lateral Compression Plate than Screws - Müller, C; Zippelius, T; Strube, P; Seeger, J B; Brinkmann, O; Matziolis, G; Wagner, A (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2018)
UNLABELLED: PURPOSE OF THE STUDY With the concept of the lateral compression plate (LLCP) a technique has been available designed to combine the advantages of a fixed-angle fixation with a complete sinking of the implant into the proximal bone. The objective of the present study was to investigate the results of the LLCP compared with classical screw osteosynthesis (SO). MATERIAL AND METHODS 31 patients with pes planovalgus who received calcaneal displacement osteotomy and osteosyntheses with screws (n = 17) or LLCP (n = 14) between 2010 and 2015 were investigated retrospectively.The ankle-hindfoot scale, Kaikkonen score, VAS, and the SF-36 were determined preoperatively as well as at the last clinical follow-up. In addition, a radiological control of osseous integration was performed in all patients 12 weeks after surgery. RESULTS With regard to clinical scores both methods depicted significant improvement. In the overall cohort there were no pseudarthroses. In the SO group 5 cases (29%) showed hardware irritation, in the LLCP group there were none. Results in the LLCP group were significantly superior in the area of the physical section of the SF 36. CONCLUSIONS Based on the results of our study, surgical treatment of stage II pes planovalgus by means of calcaneal displacement osteotomy using the LLCP is equivalent to SO with a lower incidence of hardware irritation. Key words:pes planovalgus, lateral compression plate, osteosynthesis, screw, hardware irritation. LEVEL OF EVIDENCE: Level IV, retrospective case serie.
Keywords: Male; Postoperative Complications; Bony Callus; Fracture Fixation, Internal; Bone Plates; Middle Aged; Comparative Effectiveness Research; vnitřní fixace fraktury; mužské pohlaví; pooperační komplikace; Calcaneus; srovnávací výzkum účinnosti; poranění měkkých tkání; Germany; kostní šrouby; hodnocení výsledků zdravotní péče; lidé; Soft Tissue Injuries; ženské pohlaví; kostní destičky; Humans; Německo; Osteotomy; patní kost; Flatfoot; kostní svalek; plochá noha; Outcome Assessment, Health Care; osteotomie; Female; lidé středního věku; Bone Screws